Using spatial indicators to investigate fish spawning strategies from ichthyoplankton surveys: A case study on co-occurring pelagic species in the NE Aegean Sea - STAVROULA TSOUKALI; MARIANNA GIANNOULAKI; APOSTOLOS SIAPATIS; EUDOXIA SCHISMENOU; STYLIANOS SOMARAKIS (Mediterranean Marine Science, 2019)
Multispecies ichthyoplankton associations are believed to be adaptive and their objective definition can be useful in designating species with similar or contrasting spawning strategies. In this case study, a suite of indicators, recently developed to characterize the spatial patterns of animal populations, are applied on egg abundance data of summer-spawning European anchovy (Engraulis encrasicolus), round sardinella (Sardinella aurita) and chub mackerel (Scomber colias), in an effort to identify common or contrasting spawning patterns in the North-East Aegean Sea (NEA) and their relation to the major oceanographic features of the area. A considerable increase in abundance and area of presence was observed between the early (May) and advanced (July) phase of the 2010 spawning period. The definition of major spatial patches revealed a persistent multispecies spawning location associated with the outflow of Black Sea water (BSW). A second major patch was defined for anchovy and chub mackerel in July, clearly associated with the Samothraki gyre (SG). In contrast, round sardinella spawned in coastal waters outside the SG. Surprisingly, in May 2010, the spawning intensity of anchovy was very low in the SG which was attributed to unfavorable conditions caused by the bloom of mucilage-producing phytoplankton cells. The levels of aggregation and occupation of space seemed to be adequately described by the indices of Positive, Equivalent and Spreading Area. Conclusively, many of the spatial indicators applied in this study have the potential to become important tools for studying egg distributions and the changing priorities of adult fish in selecting spawning sites.

Modelling small pelagic fish potential spawning habitats: eggs vs spawners and in situ vs satellite data - Eudoxia Schismenou; Stavroula Tsoukali; Marianna Giannoulaki; Stylianos Somarakis (Hydrobiologia, 2017)